Hubungan Indeks Massa Tubuh (IMT) dan Aktivitas Fisik Dengan Kekuatan Otot Genggam Pada Pasien Diabetes Melitus Tipe 2 di Rumah Sakit Umum Pusat Sanglah Denpasar - Dewa Ayu Sri Agung Suandewi; Susy Purnawati; Made Ratna Saraswati (E-Jurnal Medika Udayana, 2017)
Musculoskeletal disorder is one of the chronic complications of type 2 Diabetes Mellitus (T2DM), which make the patient suffered from disabilities in their daily life. The musculoskeletal system function can be measured by knowing hand grip muscle strength using handgrip dynamometer. The aim of this study was describe the relationship of BMI, and physical activity with the handgrip muscle strength in T2DM patients in Sanglah Hospital, Denpasar. A cross sectional analytic study conducted in Diabetes Centre Sanglah Hospital, between March and September 2016. Sixty one samples aged between 43-78 years old were collected using consecutive sampling. 36 samples (59.0%) had low handgrip muscle strength, 25 samples (41.0%) had moderate handgrip muscle strength, and no sample have strong handgrip muscle strength. Mean of muscle strength was 21.26 kgs (range between 13.00 kgs-33.0 kgs).There was no correlation found between BMI and handgrip muscle strength (r = -0.236, p = 0.067). There was a significant weak positive correlation between physical activity and handgrip muscle strength (r = 0.340, p = 0.007). There was no correlation found between BMI and muscle strength and there was a significant positive correlation between physical activity and the handgrip muscle strength. Keyword : Type 2 Diabetes Mellitus, handgrip muscle strength, body mass index, physical activity